Otimização do processo de obtenção de biodiesel através da adsorção de água formada durante a reação de esterificação - Lucena, Izabelly Larissa (2008)
This dissertation aimed to optimize the esterification reaction for biodiesel production using an adsorption reaction system. Adsorption was applied to remove the water formed in the process, because water deactivates the catalyst and shifts the equilibrium towards the hydrolysis reaction. Water reduces the yield of the esterification reaction, which requires high concentrations of alcohol in the reaction medium. Two experimental designs were carried out for the esterification reactions. One with and one without adsorbing the water formed in the process. In both designs, the variables temperature, catalyst concentration, and molar ratio between alcohol and fatty acid were investigated. Catalyst concentration and the alcohol to FFA molar ratio were the most statistically significant responses on conversion (within a 95% level of confidence) when the reaction was carried out without the adsorption system. The best result was obtained in experimental temperature of 110°C with a molar ratio of 9:1 and with a concentration of 1% of catalyst. Temperature and catalyst concentration were the most statistically significant variables in the experiments carried out with the adsorption system (for the confidence level of 95%). Higher temperatures and higher catalyst concentration enhanced the yield into biodiesel. The kinetic experiments showed that with the adsorption system the process became more sensitive to temperature, since the value of the apparent activation energy of the reaction was 26.66 kJ/mol and without adsorption system the apparent activation energy was 18.43 kJ/mol. GC/MS analysis showed that acidity index was very satisfactory to evaluate the yield of biodiesel., because the conversions obtained in both methods were equivalent. Density, iodine value and kinematics viscosity were within the specifications required by ANP. The methodology developed in this study resulted in conversions of oleic acid into methyl esters of 98.9% and 99.4% for the experiments performed with a molar ratio of 3:1, concentration of 1% of catalyst and temperatures of 90 and 100 ° C, respectively.